2020
DOI: 10.18502/jad.v14i3.4564
|View full text |Cite
|
Sign up to set email alerts
|

An Inventory of the Sand Flies (Diptera: Psychodidae) of Rudbar County, a New Focus of Leishmaniasis in Northern Iran, with a Taxonomic Note on the Subgenus Larroussius

Abstract: Background: Different forms of leishmaniasis are significant infectious diseases in Iran. While, Rudbar County of Gui­lan Province has been introduced as a new cutaneous leishmaniasis focus, there are few published data about the phlebotomine sand flies (Diptera: Psychodidae) of the province. Methods: To study the phlebotomine fauna of Rudbar County, the sampling was performed in 12 collection sites by light traps, sticky traps and manual aspirators throughout August–December 2015. Sand flies were remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In general, most of the suspected and infected people did not travel to leishmaniasis endemic and non-endemic areas. Therefore, due to the presence of the reservoirs (dogs and canines) and vectors (sandflies) of VL in the region (10), it could be concluded that they have probably been infected in Roudbar county.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, most of the suspected and infected people did not travel to leishmaniasis endemic and non-endemic areas. Therefore, due to the presence of the reservoirs (dogs and canines) and vectors (sandflies) of VL in the region (10), it could be concluded that they have probably been infected in Roudbar county.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study on the Phlebotomine fauna in Roudbar County, the existence of vectors of leishmaniasis was proven. Noteworthy, all collected Phlebotomus species were suspected or proven vectors of CL and/ or VL in Iran or adjoining countries (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zoonotic Cutaneous Leishmaniasis (ZCL) caused by Leishmania major Yakimoff and Schokhor, 1914 is a public health problem in several countries affecting a large number of people ( 1 ). The disease is endemic in in 18 out of 31 provinces of Iran ( 2 ). The great gerbils ( Rhombomys opimus Lichtenstein, 1823) is the main reservoir hosts of ZCL in Iran and this rodent acts as a reservoir host of ZCL in Esfahan Province, central Iran ( 1 ).…”
Section: Introductionmentioning
confidence: 99%